Mechanisms governing the accessibility of DNA damage proteins to constitutive heterochromatin - Roemer, Anastasia; Mohammed, Lanah; Strickfaden, Hilmar; Underhill, D. Alan; Hendzel, Michael J. (Frontiers in Genetics, 2022)
Chromatin is thought to regulate the accessibility of the underlying DNA sequence to machinery that transcribes and repairs the DNA. Heterochromatin is chromatin that maintains a sufficiently high density of DNA packing to be visible by light microscopy throughout the cell cycle and is thought to be most restrictive to transcription. Several studies have suggested that larger proteins and protein complexes are attenuated in their access to heterochromatin. In addition, heterochromatin domains may be associated with phase separated liquid condensates adding further complexity to the regulation of protein concentration within chromocenters. This provides a solvent environment distinct from the nucleoplasm, and proteins that are not size restricted in accessing this liquid environment may partition between the nucleoplasm and heterochromatin based on relative solubility. In this study, we assessed the accessibility of constitutive heterochromatin in mouse cells, which is organized into large and easily identifiable chromocenters, to fluorescently tagged DNA damage response proteins. We find that proteins larger than the expected 10 nm size limit can access the interior of heterochromatin. We find that the sensor proteins Ku70 and PARP1 enrich in mouse chromocenters. At the same time, MRE11 shows variability within an asynchronous population that ranges from depleted to enriched but is primarily homogeneously distribution between chromocenters and the nucleoplasm. While larger downstream proteins such as ATM, BRCA1, and 53BP1 are commonly depleted in chromocenters, they show a wide range of concentrations, with none being depleted beyond approximately 75%. Contradicting exclusively size-dependent accessibility, many smaller proteins, including EGFP, are also depleted in chromocenters. Our results are consistent with minimal size-dependent selectivity but a distinct solvent environment explaining reduced concentrations of diffusing nucleoplasmic proteins within the volume of the chromocenter.